RECONSTRUCTION OF CULTURAL JURISPRUDENCE TO STRENGTHEN THE CONSTITUTIONAL GUARANTEE OF LOCAL CULTURE IN INDONESIA - Ivan Sunata; Duski Samad; Khairul Fahmi (Universitas Nurul Jadid, 2025)
This article aims to reconstruct the cultural fiqh approach as an integrative strategy to strengthen constitutional guarantees for local culture in Indonesia. This study uses a qualitative method with a juridical-conceptual and philosophical-cultural approach to examine the relationship between Islamic law (fiqh), local culture, and state legal norms. The analysis is carried out through a literature study of classical and contemporary fiqh texts, constitutional documents, and the thoughts of progressive fiqh figures. The research findings show that fiqh has epistemological flexibility that allows accommodation to local culture through rules such as al-‘ādah muhakkamah and maqāṣid al-syarī‘ah. The Indonesian Constitution, especially Article 28I and Article 32 of the 1945 Constitution, provides a strong legal basis for the preservation of regional culture. This article formulates an integrative model between fiqh and constitutional guarantees that allows the preservation and strengthening of local culture harmoniously within the framework of Islamic values and national law